Hubungan Antara Tingkat Kekumuhan Dengan Kondisi Sosial Ekonomi Penghuni Permukiman Kumuh Di Kelurahan Pasar Gunung Tua Kabupaten Padang Lawas Utara Sumatera Utara - Upliah Nora Harahap; Lutfhi Muta’Ali; Andri Kurniawan (Jurnal Permukiman, 2024)
Pasar Gunung Tua Village has a slum area of 55.64 Ha. Extensive slum areas can cause serious health, environmental, and socioeconomic problems. The socio-economic condition of slum dwellers is generally poor due to lack of functional skills, inadequate education and low income sources.This study aims to determine the level of slums based on house building in Pasar Gunung Tua Village and identify factors that contribute to the emergence of housing slums in Pasar Gunung Tua Village, Padang Lawas Utara Regency. The approach used in this study is a quantitative approach with descriptive statistical analysis techniques.  Sampling of each neighborhood uses the Proportional Stratified Random Sampling method, while the sampling technique used for assessing houses uses Random Sampling. The data analysis used is scoring analysis, crosstab, and chi-square test using SPSS software. Based on the scoring analysis of the assessment of housing conditions, there are variations in the level of slums, namely severe, moderate, and low slums. The variables that determine the slumliness of houses using the chi-square test show that the main differentiator is related to socioeconomic factors , namely education level, employment, and income level in the Pasar Gunung Tua Village